Effectiveness of motivational interviewing at improving oral health: a systematic review - Cascaes,Andreia Morales (2014)
OBJECTIVE : To analyze the effectiveness of motivational interviewing (MI) at improving oral health behaviors (oral hygiene habits, sugar consumption, dental services utilization or use of fluoride) and dental clinical outcomes (dental plaque, dental caries and periodontal status). METHODS : A systematic search of PubMed, LILACS, SciELO, PsyINFO, Cochrane and Google Scholar bibliographic databases was conducted looking for intervention studies that investigated MI as the main approach to improving the oral health outcomes investigated. RESULTS : Of the 78 articles found, ten met the inclusion criteria, all based on randomized controlled trials. Most studies (n = 8) assessed multiple outcomes. Five interventions assessed the impact of MI on oral health behaviors and nine on clinical outcomes (three on dental caries, six on dental plaque, four on gingivitis and three on periodontal pockets). Better quality of evidence was provided by studies that investigated dental caries, which also had the largest population samples. The evidence of the effect of MI on improving oral health outcomes is conflicting. Four studies reported positive effects of MI on oral health outcomes whereas another four showed null effect. In two interventions, the actual difference between groups was not reported or able to be recalculated. CONCLUSIONS : We found inconclusive effectiveness for most oral health outcomes. We need more and better designed and reported interventions to fully assess the impact of MI on oral health and understand the appropriate dosage for the counseling interventions.